HOP, a Co-chaperone Involved in Response to Stress in Plants - Toribio, René; Mangano, Silvina; Fernández-Bautista, Nuria; Muñoz, Alfonso; Castellano, M. Mar (Frontiers in Plant Science, 2020)
Protein folding is an essential step for protein functionality. In eukaryotes this process is carried out by multiple chaperones that act in a cooperative manner to maintain the proteome homeostasis. Some of these chaperones are assisted during protein folding by different co-chaperones. One of these co-chaperones is HOP, the HSP70-HSP90 organizing protein. This assistant protein, due to its importance, has been deeply analyzed in other eukaryotes, but its function has only recently started to be envisaged in plants. In this kingdom, the role of HOP has been associated to plant response to different cellular, biotic and abiotic stresses. In this article, we analyze the current knowledge about HOP in eukaryotes, paying a special attention to the recently described roles of HOP in plants. In addition, we discuss the recent breakthroughs in the field and the possible new avenues for the study of plant HOP proteins in the future.